Potential of Chitosan and its derivatives for controlled drug release applications â A review - Safdar, R. (2019)
Recent research on the drug delivery systems exhibited tremendous improvements for several short life drugs which disappear in few minutes in harsh conditions of the Gastrointestinal tract (GIT). After years of investigations, the current drug delivery system has been improved with new advanced materials with less toxicity and better therapeutic efficiency. In this regard, new formulations consisting of drugs encapsulated with natural biodegradable copolymer, Chitosan, in the form of nanoparticles have been studied, which in turn improved the release profile of drugs. In this review, the Chitosan and its physiochemical properties, nanoparticles and their drug release mechanism and effects of modification of various drugs (antiâcancer, antiâinflammatory, antiâdiabetes, antiâinfectious drugs etc) with Chitosan and coâmaterials on their release profiles are briefly reviewed. These biodegradable polymeric nanoparticles improved the in vitro release profile of drugs and provided a way forward for further improvement of the current and conventional drug delivery systems. Â© 2018 Elsevier B.V.